Transformasi Pembelajaran Matematika melalui Pengembangan Lingkungan Belajar Interaktif bagi Guru di Kabupaten Maros - Nasrullah, Nasrullah; Khadijah, Khadijah; Liani, Ahyani Mirah; Wahyuni, Maya Sari; Fettyana, Fettyana (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2025)
The paradigm shift in 21st-century education requires mathematics teachers not only to deliver content but also to design learning experiences that are interactive, contextual, and student-centered. This community service program aimed to transform mathematics learning practices in Maros Regency by enhancing teachers’ competencies in designing interactive and dynamic digital learning environments. The program was implemented through main stages: (1) needs analysis and socialization, (2) digital learning design workshops, (3) classroom implementation and mentoring, (4) evaluation and reflection. The activity involved 30 mathematics teachers from junior and senior high schools under the Maros Mathematics Teacher Association (MGMP), facilitated by lecturers and students from Universitas Negeri Makassar. During the workshops, teachers practiced using various digital tools, like GeoGebra Classroom, Canva for Education, and Padlet, to create interactive digital student worksheets (LKPD) based on local Maros contexts. The results indicate a significant improvement in teachers’ competencies, with increase of points between pre- and post-training assessments. Digital LKPDs were produced, with most of them meeting the criteria of "good" to "very good" in terms of interactivity, conceptual clarity, and visual quality. Classroom implementation demonstrated positive changes in student engagement and learning motivation, along with greater teacher confidence in integrating technology into instruction.